Imaging of rectal cancer - Boot, J. (Radiologe, 2019)
International guidelines dictate that magnetic resonance imaging (MRI) should be part of the primary standard work up of patients with rectal cancer because MRI can accurately identify the main risk factors for local recurrence and stratify patients into a differentiated treatment. The role of endoscopic ultrasound (EUS) is restricted to staging of superficial tumors because EUS is able to differentiate between T1 and T2 rectal cancer. Recent guidelines recommend the addition of diffusion-weighted (DWI) MRI to clinical and endoscopic assessment of response to preoperative radiochemotherapy (RCT). MRI is able to identify significant tumor regression which may alter the surgical approach.